(untitled) (Journal of the College of Basic Education, 2022)
The study included the evaluation of the inhibitory activity of hot alcoholic extract and silver nanoparticles of tamarind and walnut bark plants against three types of pathogens: Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aurous. Two types of plant extracts were prepared in addition to silver nanoparticles. The chemical detection of the active compounds of the alcoholic extract of both plants was done. The results showed the presence of steroids, tannins, clacoids, saponins, flavones and alkaloids in the alcoholic extract of the walnut bark plant, while the results of the chemical detection of the tamarind plant showed the presence of flavones and alkaloids. And saponins steroids and tannins and